From fear to flow : personality and information interaction - Heinstrom, Jannica, 1970- (Chandos information professional series., 2010)
From Fear to Flow explores how personality traits may influence attitude, behaviour and reaction to information. Consideration is made for individual differences in information behaviour and reasons behind individual search differences. The book reviews personality and information behaviour and discusses how personality may influence the attitude towards information. Reaction to information is examined in contexts such as everyday life, decision-making, work, studies and human-computer interaction. Introduces a little researched area which is current and needed in our Information AgeExplores how personality traits may influence attitude, behaviour and reaction to informationProvides an overview of the psychological aspects and individual differences in information seeking behaviour and examines reasons behind individual search differences other than personality.